Sales Channels and Media Digitalization Impact on People Voluntary Savings for Retirement - Dundure, Evija; Sloka, Biruta (My University, 2019)
Due to the implementation of new technologies and orientation on digital solutions the communication and sales channels have changed dramatically. Information and client service on-line availability presents strong advantages for business, state agencies as well as customers. However, lack of personal interaction during the communication and sales process can make it difficult for people to understand and even frustrate their desire for a product or service. The purpose of the research is to analyse the digitalization impact on voluntary savings for retirement in Latvia and make comparisons with other countries. The voluntary pension schemes are the part of pension system and its third pillar created to strengthen and foster sustainability and adequacy of people income level after retirement. Main stakeholders in voluntary savings for retirement are pension funds as well as government agencies carrying out the national pension system policy. Among other motivation factors the people knowledge level about the necessity to participate in third pension level causes their willingness to create voluntary savings. Service providers chosen marketing and governments realized legislation policy impact the level of people engagement in private pensions and make a basis for people retirement period living standards. Research methods used are analysis of scientific publications and previous conducted research, analysis of statistical data and sales and communication channels in Latvia. The results of analyses show the challenges that service providers are facing and steps that should be taken to promote the voluntary savings in a digital era.
Keywords: Communication; Digitalization; Financial literacy; Pensions; Voluntary savings; Research Subject Categories::SOCIAL SCIENCES::Business and economics